2016
DOI: 10.1016/j.compstruct.2016.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Scaling effect in notched composites: The Discrete Ply Model approach

Abstract: Keywords:Size effect Open-hole tensile test Discrete Ply Modeling Experiments Finite element model a b s t r a c t Numerical and experimental investigations were carried out on the size effect in notched carbon/epoxy laminates. This paper presents a computational study of scaled open-hole tensile tests using the Discrete Ply Modeling (DPM) method, which has already proven efficient on both in-plane and out-of-plane loading cases, such as pull through, low velocity impact and compression after impact. The speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 42 publications
4
42
0
Order By: Relevance
“…For this model, the stress is averaged over this distance d 0 , called the ''average distance", in order to smooth the stress field in the surroundings of the hole/notch. One of the important issues generated by the study of holes and cracks is the scaling effect [7][8][9][10][11][12], which can be rendered by ''averaged stresses" type models even if the distance d 0 can depend on several factors [6], such as stacking sequence, material, and hole/notch size. The size effect leads, in particular, to a small hole being less penalizing than a large hole (for homothetic size of structures).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this model, the stress is averaged over this distance d 0 , called the ''average distance", in order to smooth the stress field in the surroundings of the hole/notch. One of the important issues generated by the study of holes and cracks is the scaling effect [7][8][9][10][11][12], which can be rendered by ''averaged stresses" type models even if the distance d 0 can depend on several factors [6], such as stacking sequence, material, and hole/notch size. The size effect leads, in particular, to a small hole being less penalizing than a large hole (for homothetic size of structures).…”
Section: Introductionmentioning
confidence: 99%
“…The size effect leads, in particular, to a small hole being less penalizing than a large hole (for homothetic size of structures). Numerous experimental and numerical investigations have been conducted in order to explain the physical meaning of the size effect [7][8][9][10][11][12]. For example, Wisnom et al [9,10] showed that the strength of notched composite laminates decreased when the notch size increased and concluded that the hole size effect was triggered by the presence of non-critical damage at the ply level, such as fiber failure, ply splitting, delamination or matrix cracking in the vicinity of the hole, smoothing the stress concentration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of these articles (the present article and its second part) initially developed the Discrete Ply Model method to deal with out-of-plane issues such as low energy impact [9,10] and pull-through [11]. This type of method is also efficient for in-plane stresses [12,13]. It is mainly based on a mesh imposing a priori rupture paths, which makes it possible to take splitting and intra and inter-laminar interactions into account.…”
Section: State Of the Art And Positioningmentioning
confidence: 99%